Hygiene inspections on passenger ships in Europe - an overview - Bartlett Christopher LR; Skipp Mel; Riemer Tobias; Nichols Gordon; Westacott Sandra; Mouchtouri Varvara A; Kremastinou Jenny; Hadjichristodoulou Christos (BMC, 2010)
Abstract Background Hygiene inspections on passenger ships are important for the prevention of communicable diseases. The European Union (EU) countries conduct hygiene inspections on passenger ships in order to ensure that appropriate measures have been taken to eliminate potential sources of contamination which could lead to the spread of communicable diseases. This study was implemented within the framework of the EU SHIPSAN project and it investigates the legislation applied and practices of hygiene inspections of passenger ships in the EU Member States (MS) and European Free Trade Association countries. Methods Two questionnaires were composed and disseminated to 28 countries. A total of 92 questionnaires were completed by competent authorities responsible for hygiene inspections (n = 48) and the creation of legislation (n = 44); response rates were 96%, and 75.9%, respectively. Results Out of the 48 responding authorities responsible for hygiene inspections, a routine programme was used by 19 (39.6%) of these to conduct inspections of ships on national voyages and by 26 (54.2%) for ships on international voyages. Standardised inspection forms are used by 59.1% of the authorities. A scoring inspection system is applied by five (11.6%) of the 43 responding authorities. Environmental sampling is conducted by 84.1% of the authorities (37 out of 44). The inspection results are collected and analysed by 54.5% (24 out of 44) of the authorities, while 9 authorities (20.5%) declared that they publish the results. Inspections are conducted during outbreak investigations by 75% and 70.8% of the authorities, on ships on national and international voyages, respectively. A total of 31 (64.6%) and 39 (81.3%) authorities conducted inspections during complaint investigations on ships on international and on national voyages, respectively. Port-to-port communication between the national port authorities was reported by 35.4% (17 out of 48) of the responding authorities and 20.8% (10 out of 48) of the port authorities of other countries. Conclusion This study revealed a diversity of approaches and practices in the conduct of inspections, differences in the qualifications/knowledge/experience of inspectors, the legislation applied during inspections, and the lack of communication and training among many EU countries. An integrated European inspection programme involving competent expert inspectors in each EU Member States and special training for ship hygiene delivered to crew members and inspectors would help to minimize the risk of communicable diseases. Common inspection tools at a European level for hygiene inspection practices and port-to-port communication are needed.